Optimizing The Resilience of Healthcare Workers Against The COVID-19 Pandemic - Muchtar; Ray Wagiu Basrowi (The Indonesian Journal of Community and Occupational Medicine, 2021)
Introduction: During the COVID-19 pandemic, healthcare workers have physical and psychosocial pressure in carrying out their work. The requirement for healthcare workers in dealing with the pandemic is so high, the identification process for the resilience of healthcare workers is not going well. The purpose of this article is to review about how to optimize the resilience of healthcare workers exposed to COVID-19 outbreak working conditions. Methods: This literature review is conducted in October 2021. Research related to the resilience of healthcare workers during COVID-19 Pandemic by using valid keywords, including resilience, healthcare workers, COVID-19 through ProQuest, ScienceDirect and SpingerLink. Results: A total of 10 articles were selected for the literature review. The process of self-reflection is one of the important things for healthcare workers. Optimizing relisience of healthcare workers by carrying out an efficient division of tasks to reduce workloads, give more attention to their needs, provide training and knowledge about digital applications to increase capacity in carrying out their work, provide mental health support for healthcare workers and creating a safe and comfortable work environment for them. Conclusions: Maintaining health during the COVID-19 pandemic is an important thing that needs to be done by healthcare workers. Stress management is an important factor in dealing with a pandemic. Create an assessment of the resilience of healthcare workers by detecting gaps, determining priorities, developing plans to prevent psychosocial hazards at all levels both individual and organizational levels.